PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS, DAN LEVERAGE TERHADAP MANAJEMEN LABA - Muhamad Eko Wahyu Umaryadi; Eko Edy Susanto; Henny Okta Piyani; Dina Grease Irawati Idiah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study examines whether managerial ownership, institutional ownership, profitability, and leverage are associated with earnings management among consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach was employed, utilizing purposive sampling to include only firms with complete data. The analysis was conducted using multiple linear regression. The results indicate that both managerial and institutional ownership exhibit a positive and statistically significant relationship with earnings management practices. In contrast, performance measures (profitability) and capital structure (leverage) show no significant effect. These findings suggest that ownership structure alone may be insufficient to restrain opportunistic financial reporting behavior, while profitability and debt levels do not appear to be the primary drivers of earnings management within this sample.